Solve for x

x=-y+\sqrt{5}<br/>x=-\left(y+\sqrt{5}\right)

$x=−y+5 $

$x=−(y+5 )$

$x=−(y+5 )$

Solve for y

y=-x+\sqrt{5}<br/>y=-\left(x+\sqrt{5}\right)

$y=−x+5 $

$y=−(x+5 )$

$y=−(x+5 )$

Graph

Copy

Copied to clipboard

x+y=\sqrt{5} x+y=-\sqrt{5}

Take the square root of both sides of the equation.

x+y-y=\sqrt{5}-y x+y-y=-\sqrt{5}-y

Subtract y from both sides of the equation.

x=\sqrt{5}-y x=-\sqrt{5}-y

Subtracting y from itself leaves 0.

x=-y+\sqrt{5}

Subtract y from \sqrt{5}.

x=-y-\sqrt{5}

Subtract y from -\sqrt{5}.

x=-y+\sqrt{5} x=-y-\sqrt{5}

The equation is now solved.

y+x=\sqrt{5} y+x=-\sqrt{5}

Take the square root of both sides of the equation.

y+x-x=\sqrt{5}-x y+x-x=-\sqrt{5}-x

Subtract x from both sides of the equation.

y=\sqrt{5}-x y=-\sqrt{5}-x

Subtracting x from itself leaves 0.

y=-x+\sqrt{5}

Subtract x from \sqrt{5}.

y=-x-\sqrt{5}

Subtract x from -\sqrt{5}.

y=-x+\sqrt{5} y=-x-\sqrt{5}

The equation is now solved.

Examples

Quadratic equation

{ x } ^ { 2 } - 4 x - 5 = 0

$x_{2}−4x−5=0$

Trigonometry

4 \sin \theta \cos \theta = 2 \sin \theta

$4sinθcosθ=2sinθ$

Linear equation

y = 3x + 4

$y=3x+4$

Arithmetic

699 * 533

$699∗533$

Matrix

\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]

$[25 34 ][2−1 01 35 ]$

Simultaneous equation

\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.

${8x+2y=467x+3y=47 $

Differentiation

\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }

$dxd (x−5)(3x_{2}−2) $

Integration

\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x

$∫_{0}xe_{−x_{2}}dx$

Limits

\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}

$x→−3lim x_{2}+2x−3x_{2}−9 $